Influence of female sex and fertile age on neuromyelitis optica spectrum disorders. (July 2017) - Borisow, Nadja; Kleiter, Ingo; Gahlen, Anna; Fischer, Katrin; Wernecke, Klaus-Dieter; Pache, Florence; Ruprecht, Klemens; Havla, Joachim; Krumbholz, Markus; Kümpfel, Tania; Aktas, Orhan; Ringelstein, Marius; et al.
Background: Gender and age at onset are important epidemiological factors influencing prevalence, clinical presentation, and treatment response in autoimmune diseases. Objective: To evaluate the impact of female sex and fertile age on aquaporin-4-antibody (AQP4-ab) status, attack localization, and response to attack treatment in patients with neuromyelitis optica (NMO) and its spectrum disorders (neuromyelitis optica spectrum disorder (NMOSD)). Methods: Female-to-male ratios, diagnosis at last visit (NMO vs NMOSD), attack localization, attack treatment, and outcome were compared according to sex and age at disease or attack onset. Results: A total of 186 NMO/SD patients (82% female) were included. In AQP4-ab-positive patients, female predominance was most pronounced during fertile age (female-to-male ratio 23:1). Female patients were more likely to be positive for AQP4-abs (92% vs 55%; p < 0.001). Interval between onset and diagnosis of NMO/SD was longer in women than in men (mean 54 vs 27 months; p = 0.023). In women, attacks occurring ⩽40 years of age were more likely to show complete remission ( p = 0.003) and better response to high-dose intravenous steroids ( p = 0.005) compared to woman at >40 years. Conclusion: Our data suggest an influence of sex and age on susceptibility to AQP4-ab-positive NMO/SD. Genetic and hormonal factors might contribute to pathophysiology of NMO/SD.